Kebijakan Sekolah Tentang Inovasi Kegiatan Ekstrakurikuler Di SMP Swasta Budisatrya Medan - Ahmad Mukhlasin; Sri Andriani; Rismoninta Padang; Abdul Rohim Husaini Wijaya (Universitas Palan, 2024)
Extracurricular activities are a series of teaching and learning activity programs outside programmed class hours, which are intended to increase students' horizons of thinking, foster students' talents and interests as well as a spirit of community service. This research uses a qualitative research method which can be understood as a research procedure that utilizes descriptive data in the form of written or spoken words from people and actors who can be observed. Based on the results of research on school policies regarding innovation in extracurricular activities at Budisatrya Middle School, the development of innovation in extracurricular activities at Budisatrya Middle School, extracurricular activities at Budisatrya Middle School increased with the presence of tahsin, tahfidz and multimedia extracurricular activities.